Bachelor of nursing students' experiences of a longitudinal team training intervention and the use of teamwork skills in clinical practice-A qualitative descriptive study - Tore Karlsen; Marie Louise Hall‐Lord; Sigrid Wangensteen; Randi Ballangrud (Wiley, 2023)
Abstract Aims To describe nursing students' experiences of a TeamSTEPPS® longitudinal team training program and the application of teamwork skills in clinical practice. Design A descriptive qualitative design. Methods Overall, 22 nursing students participated in six online focus group interviews after attending a TeamSTEPPS® team training program from their first semester. The data were audio‐recorded, transcribed and analysed using inductive content analysis and reported following the COREQ guidelines. The focus group interviews took place in the students' fifth's semester. Results The main category "Learning teamwork is not an event; it's a journey" emerged from 3 generic categories and 12 subcategories. The participants reported that grasping the relevance of team training and the use of teamwork skills takes time. Utilizing these skills improved their awareness of being a team member and facilitated learning. Conclusion Team training raised the participants' awareness of teamwork as an essential component of being a professional nurse. Additionally, understanding the complexity of teamwork takes time.